Perception of Tooth Carving Sessions among Undergraduate Dental Students within the Faculty of Dentistry/University of Benghazi - E. S. Eltira, Aziza; Buzaribah, Khadeejah; Areibi, Aisha (Libyan Journal of Dentistry, 2024)
Background: In most dental schools, dental anatomy is taught in both theoretical and practical sessions during the first years of the Bachelor of Dental Surgery (BDS). This comprehensive course equips students with essential knowledge about dental morphology and occlusion. Furthermore, it serves as the fundamental basis for various clinical disciplines within dentistry, particularly those related to tooth restoration. Aim: The study aimed to evaluate dental students’ response to tooth carving sessions using wax blocks within the BDS curriculum at the Faculty of Dentistry in Benghazi and to assess the benefit of these sessions in improving their knowledge, and understanding of tooth morphology. Methods: A three-month cross-sectional descriptive study was conducted in 2022 among 474 undergraduate dental students at the Faculty of Dentistry in Benghazi. We employed a convenience sampling approach to collect the data. The questionnaire was prepared using a semi-structured proforma, which included questions about participants’ perceptions of tooth carving. Participants received a Google Form link through the telegram channel of the students. Descriptive statistics, including mean, standard deviation, percentage, and frequency were calculated using the SPSS 21. Results: A total of 474 dental students participated in this study. Among them 94% practiced tooth carving using wax blocks during their practical sessions of dental anatomy. More than 70% of participants agreed that tooth carving enhanced their understanding of precise tooth morphology, dental anatomy, and proper occlusion relationships. Interestingly, 63% of the participants believed that live demonstration assisted with step-by-step video tutorials would be more effective in practicing tooth carving. Conclusion: Based on the results, it is evident that most students at the Dental Faculty of Benghazi recognize the significant importance of tooth carving in their educational journey as future dental practitioners. This valuable data can inform the development of dental education programs, ensuring continued emphasis on teaching tooth carving during the undergraduate stage. However, as we move forward, exploring innovative approaches becomes essential. Incorporating newer techniques such as computer-aided platforms and video tutorials could enhance student engagement and provide a deeper understanding of tooth morphology and anatomy.